After‐hours emergency department care: Does time or day of arrival affect survival?. (9th September 2020) - Rolls, David A; Khanna, Sankalp; Boyle, Justin; Xie, Yang; Good, Norm; Romeo, Michelle; Bell, Anthony
Abstract: Objective: To determine whether after‐hours presentation to EDs is associated with differences in 7‐day and 30‐day mortality. The influence of patient case‐mix and workforce staffing differences are also explored. Methods: We conducted a retrospective observational study of 3.7 million ED episodes across 30 public hospitals in Queensland, Australia during May 2013–September 2015 using routinely collected hospital data linked to hospital staffing data and the death registry. Episodes were categorised as within/after‐hours using time of presentation. Staffing was derived from payroll records and explored by defining 11 staffing ratios. Results: Weekend presentation was slightly more associated (7‐day mortality odds ratio 1.05, 95% confidence interval [CI] 1.01–1.10) or no more associated (30‐day mortality odds ratio 1.01, 95% CI 0.98–1.03) with death than weekday presentation. When weeknights are included in the 'after‐hours' period, odds ratios are smaller, so that after‐hours presentation is no more associated (7‐day mortality odds ratio 1.03, 95% CI 0.99–1.08) or less associated (30‐day mortality odds ratio 0.95, 95% CI 0.93–0.97) with death. No significant after‐hours patient case‐mix differences were observed between weekday and weekend presentations for 7‐day mortality. In other combinations of outcome and after‐hours definition, some differences (especially measures relating to severity of presenting condition) were found. Staffing ratios were not strongly associated with any within/after‐hours differences in ED mortality. Conclusions: After‐hours presentation on the weekend to an ED is associated with higher 7‐day mortality even after controlling for case‐mix.